An analytical study of the reality of environmental and health awareness in matches according to sustainable development among female university volleyball team players - Al-Khamasi, Asst.Prof.Dr.Maysaloon Zuhair Hussein; Hassan, Asst.L.Ahmed Hamza; Ibrahi, Prof.Dr. Firas Suhail; Al-Dulaimi, Prof. Dr. Naheda Abdul Zaid (Sulaimani Journal for Humanities, 2026)
This research aimed to identify the level of environmental and health awareness among female university volleyball team players in matches, in accordance with sustainable development principles. It also sought to determine the differences in environmental and health awareness among these players. The researchers employed a descriptive methodology, utilizing both survey and case study approaches, as these were best suited to the research objectives. The research population consisted of 134 female university volleyball team players participating in the Iraqi Universities Volleyball Championship. The research sample comprised 40 players, randomly selected from the population, representing 29.851% of the total. Environmental and health awareness scales were used. A pilot study was conducted, followed by the scientific validation of the scales (validity, reliability, and objectivity). Appropriate statistical methods were used to analyze the results. Based on these findings, the researchers concluded that the female university volleyball team players (the research sample) possessed a good level of environmental and health awareness. Furthermore, the levels of environmental and health awareness were found to be relatively similar among the female volleyball players (the research sample). In light of these conclusions, the researchers recommended the importance of focusing on this aspect. Environmental and health awareness for female university volleyball players, with a great need to pay attention to clarifying and disseminating information on environmental and health awareness in volleyball and other sports.
Keywords: Reality; environmental awareness; health awareness; sustainable development; volleyball